zapisz w prostszej postaci :
a)(a+\frac{2}{a})^{2} - (\frac{a^{2}-2}{a})^{2}=
b)
a)b)
" Life is not a problem to be solved but a reality to be experienced! "
© Copyright 2013 - 2025 KUDO.TIPS - All rights reserved.
a)
![(a+\frac{2}{a})^{2} - (\frac{a^{2}-2}{a})^{2}= (a+\frac{2}{a})^{2} - (\frac{a^{2}-2}{a})^{2}=](https://tex.z-dn.net/?f=%28a%2B%5Cfrac%7B2%7D%7Ba%7D%29%5E%7B2%7D+-+%28%5Cfrac%7Ba%5E%7B2%7D-2%7D%7Ba%7D%29%5E%7B2%7D%3D)
![(\frac{a^2+2}{a})^{2} - \frac{a^4-4a^2+4}{a^2}= (\frac{a^2+2}{a})^{2} - \frac{a^4-4a^2+4}{a^2}=](https://tex.z-dn.net/?f=%28%5Cfrac%7Ba%5E2%2B2%7D%7Ba%7D%29%5E%7B2%7D+-+%5Cfrac%7Ba%5E4-4a%5E2%2B4%7D%7Ba%5E2%7D%3D)
![\frac{a^4+4a^2+4}{a^2} - \frac{a^4-4a^2+4}{a^2}= \frac{a^4+4a^2+4}{a^2} - \frac{a^4-4a^2+4}{a^2}=](https://tex.z-dn.net/?f=%5Cfrac%7Ba%5E4%2B4a%5E2%2B4%7D%7Ba%5E2%7D+-+%5Cfrac%7Ba%5E4-4a%5E2%2B4%7D%7Ba%5E2%7D%3D)
![\frac{a^4+4a^2+4-a^4+4a^2-4}{a^2}= \frac{a^4+4a^2+4-a^4+4a^2-4}{a^2}=](https://tex.z-dn.net/?f=%5Cfrac%7Ba%5E4%2B4a%5E2%2B4-a%5E4%2B4a%5E2-4%7D%7Ba%5E2%7D%3D)
![\frac{8a^2}{a^2}=8 \frac{8a^2}{a^2}=8](https://tex.z-dn.net/?f=%5Cfrac%7B8a%5E2%7D%7Ba%5E2%7D%3D8)
![(\frac{3}{x}+\frac{x}{3})^{2}-( \frac{x}{3}-\frac{3}{x})^{2}= (\frac{3}{x}+\frac{x}{3})^{2}-( \frac{x}{3}-\frac{3}{x})^{2}=](https://tex.z-dn.net/?f=%28%5Cfrac%7B3%7D%7Bx%7D%2B%5Cfrac%7Bx%7D%7B3%7D%29%5E%7B2%7D-%28+%5Cfrac%7Bx%7D%7B3%7D-%5Cfrac%7B3%7D%7Bx%7D%29%5E%7B2%7D%3D)
![(\frac{9}{3x}+\frac{x^2}{3x})^{2}-( \frac{x^2}{3x}-\frac{9}{3x})^{2}= (\frac{9}{3x}+\frac{x^2}{3x})^{2}-( \frac{x^2}{3x}-\frac{9}{3x})^{2}=](https://tex.z-dn.net/?f=%28%5Cfrac%7B9%7D%7B3x%7D%2B%5Cfrac%7Bx%5E2%7D%7B3x%7D%29%5E%7B2%7D-%28+%5Cfrac%7Bx%5E2%7D%7B3x%7D-%5Cfrac%7B9%7D%7B3x%7D%29%5E%7B2%7D%3D)
![(\frac{9+x^2}{3x})^{2}-( \frac{x^2-9}{3x})^{2}= (\frac{9+x^2}{3x})^{2}-( \frac{x^2-9}{3x})^{2}=](https://tex.z-dn.net/?f=%28%5Cfrac%7B9%2Bx%5E2%7D%7B3x%7D%29%5E%7B2%7D-%28+%5Cfrac%7Bx%5E2-9%7D%7B3x%7D%29%5E%7B2%7D%3D)
![\frac{81+18x^2+x^4}{9x^2}-\frac{x^4-18x^2+81}{9x^2}= \frac{81+18x^2+x^4}{9x^2}-\frac{x^4-18x^2+81}{9x^2}=](https://tex.z-dn.net/?f=%5Cfrac%7B81%2B18x%5E2%2Bx%5E4%7D%7B9x%5E2%7D-%5Cfrac%7Bx%5E4-18x%5E2%2B81%7D%7B9x%5E2%7D%3D)
![\frac{81+18x^2+x^4-x^4+18x^2-81}{9x^2}= \frac{81+18x^2+x^4-x^4+18x^2-81}{9x^2}=](https://tex.z-dn.net/?f=%5Cfrac%7B81%2B18x%5E2%2Bx%5E4-x%5E4%2B18x%5E2-81%7D%7B9x%5E2%7D%3D)
![\frac{36x^2}{9x^2}=4 \frac{36x^2}{9x^2}=4](https://tex.z-dn.net/?f=%5Cfrac%7B36x%5E2%7D%7B9x%5E2%7D%3D4)
b)